Institutional Change On First Nations: Examining Factors Influencing First Nations’ Adoption of the Framework Agreement on First Nation Land Management - Doidge, Mary; Deaton, B. James; Woods, Bethany (Journal of Aboriginal Economic Development, 2013)
In 1999 the Canadian Federal government passed the First Nations Land Management Act, ratifying the Framework Agreement on First Nation Land Management signed by the government and 14 original signatory First Nations in 1996. This Agreement allows First Nations to opt out of the 34 land code provisions of the Indian Act and develop individual land codes, and has been promoted as a means of increasing First Nation autonomy and facilitating economic growth and development on reserve lands. There are currently 77 First Nation signatories to the Agreement, 39 with operational independent land codes. This paper is the first to empirically examine factors that may influence a First Nation's decision to become signatory to the Framework Agreement. A unique dataset characterizing each First Nation by socio-economic and demographic characteristics is used with a probit model to determine the effects of these characteristics on the probability of First Nation adoption of the Agreement. The results of this study indicate that proximity to an urban centre positively affects the probability that a First Nation will adopt. However, the statistical strength of this finding is sensitive to the inclusion of an education variable in the regression.